Sulfur amino acid restriction–induced changes in redox‐sensitive proteins are associated with slow protein synthesis rates. Issue 1 (29th January 2018) - Nichenametla, Sailendra N.; Mattocks, Dwight A.L.; Malloy, Virginia L.; Pinto, John T.
Abstract: The mechanisms underlying life span extension by sulfur amino acid restriction (SAAR) are unclear. Cysteine and methionine are essential for the biosynthesis of proteins and glutathione (GSH), a major redox buffer in the endoplasmic reticulum (ER). We hypothesized that SAAR alters protein synthesis by modulating the redox milieu. Male F344‐rats were fed control (CD: 0.86% methionine without cysteine) and SAAR diets (0.17% methionine without cysteine) for 12 weeks. Growth rates, food intake, cysteine and GSH levels, proteins associated with redox status and translation, and fractional protein synthesis rates (FSRs) were determined in liver. Despite a 40% higher food intake, growth rates for SAAR rats were 27% of those fed CD. Hepatic free cysteine in SAAR rats was 55% compared with CD rats. SAAR altered tissue distribution of GSH, as hepatic and erythrocytic levels were 56% and 196% of those in CD rats. Lower GSH levels did not induce ER stress (i.e., unchanged expression of Xbp1 s, Chop, and Grp78 ), but activated PERK and its substrates eIF2‐α and NRF2. SAAR‐induced changes in translation‐initiation machinery (higher p‐eIF2‐α and 4E‐BP1, and lower eIF4G‐1) resulted in slower protein synthesis rates (53% of CD). Proteins involved in the antioxidant response (NRF2, KEAP1, GCLM, and NQO1) and protein folding (PDI and ERO1‐α) were increased in SAAR. Lower FSR and efficient protein folding might be improving proteostasis in SAAR.